Evaluation of pulmonary artery stiffness and right ventricle functions in polycythemia vera patients by transthoracic echocardiography - Karaca, Yuecel; Hidayet, Siho; Bayramoglu, Adil; Yildirim, Erkan; Berber, Ilhami; Guven, Fatih; Hidayet, Emine (Wiley, 2023)
IntroductionPolycythemia vera (PV) is known to be a subgroup of chronic myeloproliferative neoplasms and is recognized as a cause of pulmonary hypertension (PH). Pulmonary artery stiffness (PAS) is a relatively new noninvasive echocardiographic index developed to evaluate the structural features and functions of the pulmonary vascular bed. In this study, we aimed to evaluate right ventricular (RV) functions and PAS in PV patients and healthy controls. MethodsA group of 65 consecutive PV patients and 40 healthy controls were included in the study. RV global longitudinal strain (RVGLS) and RV free wall longitudinal strain were (RVFwLS) evaluated using two-dimensional (2D) strain echocardiography. RV volume, systolic and diastolic functions were evaluated with three-dimensional (3D) echocardiography. PAS was calculated using the maximum frequency shift (MFS) and acceleration time of the pulmonary artery flow trace. ResultsPAS values were significantly higher in the PV group than in the control group (25.2 +/- 5.2 vs. 18.2 +/- 4.2, p < .001). We found that tricuspid annular plane systolic excursion (TAPSE) (p < .001), RV fractional area change (p < .001) and RV ejection fraction (p < .001) measurements evaluated by 3D echocardiography were significantly lower in the PV group. ConclusionIn our study, PAS values were higher in PV patients than in the healthy control group. Patients with PV may have subclinical RV dysfunction, and PAS value can be used in the early diagnosis of PH and RV dysfunction in this patient group.
Keywords: three-dimensional echocardiography; polycythemia vera; pulmonary artery stiffness; right ventricular function